PENGARUH DIGITALISASI AKUNTANSI DAN LITERASI KEUANGAN DIGITAL TERHADAP PRESTASI KERJA/KINERJA UMKM DI KECAMATAN PRAYA BARAT LOMBOK TENGAH: The Effect Of Accounting Digitalization And Digital Financial Literacy On Work Achievement/Performance Of MSMES In Praya Barat District, Central Lombok - Kartini, Endang; Mimbar, Lalu; Izrawati, Izrawati (Ganec Swara, 2026)
The purpose of this study was to analyze accounting digitalization and digital financial literacy, each measured by the following indicators: Perception of Accounting Digitalization, Experience with Accounting Digitalization, Challenges in Implementing Accounting Digitalization, Knowledge, Skills/Experience, Behavior, and Perception and Trust, all significantly influencing both simultaneous and partial work performance of MSMEs in West Praya District, Central Lombok. The population consisted of four MSME clusters with 1,314 samples, of which 93 were taken. The results showed that each of the seven independent variable indicators significantly influenced both partial and simultaneous work performance of MSMEs. The coefficient values ​​for all seven variable indicators were positive, indicating a unidirectional relationship between the seven variables and MSME work performance. The strength of the relationship between the independent and dependent variables, indicated by the R value of 71.6%, indicates a very strong correlation. Variations in MSME performance are explained by variations in the seven independent variable indicators, accounting for 87.4%, as indicated by the adjusted R2. The remaining 12.6% is explained by factors outside the model. It was identified that in predicting the dependent variable, as seen from the Standard Error of Estimate (SEE) value of 0.138, a smaller SEE value indicates a more accurate regression model in predicting the dependent variable.